2015
DOI: 10.1007/s13593-015-0291-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel sub-phylum method discriminates better the impact of crop management on soil microbial community

Abstract: Soil microorganisms such as mycorrhizae and plant-growth-promoting rhizobacteria have beneficial effects on crop productivity. Agricultural practices are known to impact soil microbial communities, but past studies examining this impact have focused mostly on one or two taxonomic levels, such as phylum and class, thus missing potentially relevant information from lower levels. Therefore, we propose here an original, sub-phylum method for studying how agricultural practices modify microbial communities. This me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Moreover, the taxonomical level used to describe and compare samples is crucial to spot differences. Two recent studies observed variation between sample groups only at the genus or lower taxonomical levels, while no differences were observed at the phylum level (Degrune et al, 2015;Schmidt et al, 2014a). Both publications underlined that the use of the genus or lowest possible taxonomical level could be more appropriate to detect differences in microbial communities.…”
Section: Opportunities For Biocontrol Research In the Microbiome Eramentioning
confidence: 99%
“…Moreover, the taxonomical level used to describe and compare samples is crucial to spot differences. Two recent studies observed variation between sample groups only at the genus or lower taxonomical levels, while no differences were observed at the phylum level (Degrune et al, 2015;Schmidt et al, 2014a). Both publications underlined that the use of the genus or lowest possible taxonomical level could be more appropriate to detect differences in microbial communities.…”
Section: Opportunities For Biocontrol Research In the Microbiome Eramentioning
confidence: 99%
“…This might be due to the CF agricultural practices, including mineral fertilization and conventional tillage. Both practices have been reported to increase soil microbial size [15] and diversity [43] by increasing the availability of easily assessable nutrients and stimulating degradation of soil organic matter. Therefore, we propose that application of chemicals (e.g., pesticides) may be the main factor that alters soil microbial alpha diversity while other agricultural practices (e.g., tillage, straw mulching, and fertilization) have smaller effects on soil microbial alpha diversity at our experimental site.…”
Section: Characteristics Of the Soil Microbial Community Under Differmentioning
confidence: 99%
“…These investigations have identified that microbial attributes could reflect ecosystem processes such as crop productivity [3], the regulation of decomposition [4], nutrient cycling [5] and protection against soil-borne pathogens [6]. Several studies have shown that agricultural Sustainability 2018, 10, 3825 2 of 16 practices have significant influences on soil microbial communities and composition, including the tillage regime [7], fertilization [8], monoculture [9], crop residue management [10] and plant protection schemes [11]. Hence, the soil microbial community could be shifted to a positive organization for plant production and ecosystem sustainability by suitable agricultural practices [4].…”
Section: Introductionmentioning
confidence: 99%